Dysfunctional Audit Behavior Determinants - YESSIE, Afly (PT Keberlanjutan Strategis Indonesia, 2021)
This study aims to test several hypotheses regarding the influence of turnover intention, performance auditor, organizational commitment, locus of control and Times budget pressure on dysfunctional audit behavior. This research was conducted on auditors working in the Public Accounting Firm (KAP) Jakarta registered in Indonesian Institute of Public Accountants (IAPI) by using the dissemination of questionnaires. This study indicates that turnover intention, performance audit, and time budget pressure have a positive and significant effect on the dysfunctional audit behavior, while the locus of control and organizational commitment negatively affect the dysfunctional audit behavior. This research contributes to the development of science, especially in the field of auditing, the acceptance of dysfunctional audit behavior. The results of this study are also expected to be used by public accounting firms to consider when to hire new auditors so that companies can prefer those who have a high locus of control and have a high organizational commitment.